2014
DOI: 10.1007/s12020-014-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones regulate skeletal muscle regeneration after acute injury

Abstract: We evaluated the effects of hypo- and hyperthyroid statuses during the initial phase of skeletal muscle regeneration in rats. To induce hypo- or hyperthyroidism, adult male Wistar rats were treated with methimazole (0.03%) or T4 (10 μg/100 g), respectively, for 10 days. Three days before sacrifice, a crush injury was produced in the solear muscles of one half of the animals, while the other half remained intact. T3, T4, TSH, and leptin serum levels were not affected by the injury. Serum T3 and T4 levels were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Thyrotoxicosis is known to be a risk factor for hypercalcemia, osteoporosis and increased bone turnover 45. A study investigating correlations between thyroid hormone levels and skeletal muscle regeneration found that high serum T3 and T4 levels could interfere with the inflammatory process following muscle injuries through up-regulation of macrophage accumulation and cell infiltration 46. The detected effect of rs2001616 polymorphisms could therefore be due to up-regulation of thyroid hormone production in carriers of the variant allele.…”
Section: Discussionmentioning
confidence: 99%
“…Thyrotoxicosis is known to be a risk factor for hypercalcemia, osteoporosis and increased bone turnover 45. A study investigating correlations between thyroid hormone levels and skeletal muscle regeneration found that high serum T3 and T4 levels could interfere with the inflammatory process following muscle injuries through up-regulation of macrophage accumulation and cell infiltration 46. The detected effect of rs2001616 polymorphisms could therefore be due to up-regulation of thyroid hormone production in carriers of the variant allele.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Ζ παξαπάλσ «θαξδηαθή αλεπάξθεηα πςειήο παξνρήο» εκθαλίδεηαη ζπλήζσο ζε αζζελείο κηθξήο ειηθίαο κε ζνβαξφ θαη καθξνρξφλην ππεξζπξενεηδηζκφ απνπζία ππνθείκελεο θαξδηνπάζεηαο. 118,162 Έλα κηθξφ πνζνζηφ αζζελψλ, θπξίσο ειηθησκέλνη κε θνιπηθή καξκαξπγή ή ππνθείκελε θαξδηνπάζεηα, αλαπηχζζεη θαξδηαθή αλεπάξθεηα κε κεησκέλε ζπζηαιηηθφηεηα θαη θιάζκα εμψζεζεο θαη απμεκέλσλ δηαζηάζεσλ αξηζηεξή θνηιία. 27 Ζ κνξθή απηή ηεο ζπζηνιηθήο δπζιεηηνπξγίαο ζπλήζσο αληηζηξέθεηαη κε ηελ απνθαηάζηαζε ηεο ζπξενεηδηθήο ιεηηνπξγίαο.Ο ιφγνο γηα ηνλ νπνίν νξηζκέλνη αζζελείο αλαπηχζζνπλ «ππεξζπξενεηδηθή κπνθαξδηνπάζεηα» θαη πξνρσξεκέλε θαξδηαθή αλεπάξθεηα παξακέλεη άγλσζηνο.…”
Section: καργηακδ δκγζλχδη σοτ τπδρθτρδοδηγημοτunclassified